2008
DOI: 10.1149/1.2840462
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Pitting Corrosion in Stainless Steel 304 L During Proton Irradiation

Abstract: In 0.1 M sodium chloride, proton irradiation resulted in a 220 mV increase in the pitting potential of stainless steel 304 L ͑0.425 vs 0.644 V saturated calomel electrode͒. In addition, the passive region of the polarization curve during irradiation was associated with a drop in metastable pitting activity by a factor of 100. Mott-Schottky experiments in pH 1.6 H 2 SO 4 found that irradiation was associated with an increase in oxygen vacancy concentration ͑V O = 2.94 ϫ 10 21 vs 3.41 ϫ 10 21 cm −3 ͒. However, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The semiconducting surface passive films respond spontaneously to illumination (Fujimoto and Tsuchiya 2007), thus providing significance to the present theme of work. The second reason was the more insightful and straightforward one, based on the fact that a number of investigators have reported a decrease in the corrosion rates and a reduced probability of localized corrosion upon ultraviolet (UV) illumination of SS (typically UNS S30400) in neutral chloride solutions (Lenhart et al 1987;MacDonald and Heaney 2000;Moussa and Hocking 2001;Fujimoto and Tsuchiya 2007;Lillard and Vasquez 2008). Quite the reverse, reports of an accelerating effect of UV illumination on the corrosion of certain other alloys such as copper and zinc have also been made (Burleigh et al 2003; Thompson and Burleigh 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The semiconducting surface passive films respond spontaneously to illumination (Fujimoto and Tsuchiya 2007), thus providing significance to the present theme of work. The second reason was the more insightful and straightforward one, based on the fact that a number of investigators have reported a decrease in the corrosion rates and a reduced probability of localized corrosion upon ultraviolet (UV) illumination of SS (typically UNS S30400) in neutral chloride solutions (Lenhart et al 1987;MacDonald and Heaney 2000;Moussa and Hocking 2001;Fujimoto and Tsuchiya 2007;Lillard and Vasquez 2008). Quite the reverse, reports of an accelerating effect of UV illumination on the corrosion of certain other alloys such as copper and zinc have also been made (Burleigh et al 2003; Thompson and Burleigh 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been applied to austenitic stainless steel and related (e.g. Ni-base) alloys [13][14][15].…”
mentioning
confidence: 99%
“…In the circuits, R s is the solution resistance; R f is the resistance of passive film; W is the Warburg impedance; and Q f represents the passive film capacitance. The presence of Warburg impedance in a passive system was commonly believed to be related to the vacancy migration under the electric field across the passive film [24], which has been widely reported in the investigations on austenitic stainless steels [24][25][26][27]. The presence of Warburg impedance indicated that the corrosion process of 316L was controlled not only by a charge transfer process but also by a diffusion control process.…”
Section: Eis Resultsmentioning
confidence: 90%